Perancangan Power Bank Dengan Memanfaatkan Tenaga Matahari (Universitas Hasyim Asy`ari, 2022)
Mobile is one of the many electronic devices that have important functions for human life. The average human being today must have a cell phone. Mobile phones require electrical energy. Mobile power comes from the battery. Like other electronic devices, the energy source stored in the cellphone battery only lasts for a few minutes and must be charged before the cellphone is used for activities again. For cellphone users with continuous use (such as games, traveling, social media, etc.), it will be a problem and will hinder or hinder use as communication with each other and inhibit activities, so in this case the author provides a solution by making a Power Bank Design using Solar Cell power as the main source of electrical power.